Intuitive Thinking Styles and the Art of Questioning Practices among Public Secondary School Teachers - Gloryfel M. Villarente; Josephine B. Baguio (Archives of Current Research International, 2025)
This study aimed to determine the significant relationship between intuitive thinking styles and the art of questioning practices among public secondary school teachers in Mati Central District, Division of Mati City. A descriptive-correlational research design was employed, with a sample of 137 public secondary school teachers in Mati Central District, Division of Mati City. Data were gathered through standardized questionnaires administered via face-to-face surveys. The data were analyzed using mean, standard deviation (SD), Pearson product-moment correlation, and multiple linear regression analyses. The findings revealed that teachers’ intuitive thinking styles and their art of questioning practices were very extensive. Correlation analysis revealed a positive significant relationship between teachers’ intuitive thinking styles and their art of questioning practices (r=0.60; p=0.000). Additionally, the study found that teachers’ intuitive thinking styles significantly influenced their art of questioning practices (r=0.62; p=0.000). It is recommended that school administrators and teacher training programs emphasize the development of intuitive questioning techniques through targeted professional development initiatives. Providing teachers with training and resources to enhance their intuitive thinking will enable them to create more engaging and effective classroom discussions, ultimately improving student learning outcomes.